Mengupas Manajemen Pembelajaran I’dadiyah Pesantren Nurul Jadid Dalam Bina Baca Al-Quran Dan Furudul ‘Ainiyah - Moh. Rofiki; Jamilatun Hasanah (Universitas Yudharta Pasuruan, 2021)
This study aims to analyze and describe how the implementation of learning management in the I'dadiyah Islamic Boarding School Nurul Jadid Az-Zainiyah Region. This study used a qualitative approach to the type of case study, with the research site at I'dadiyah Pesantren Nurul Jadid. The results showed that the implementation of learning management at the I'dadiyah institution consisted of the following steps: learning planning, through planning programs that have been made based on the pesantren curriculum in Nurul Jadid Islamic Boarding School and compiling a program that will be achieved every month and every quarter. , organizing learning, carried out by distributing tasks to teachers along with study hours and learning materials that focus only on building reading the al-quran and furudul 'ainiyah followed by compiling a learning schedule and examinations. implementation of learning, through mental and physical processes of students while honing their development; monitoring of learning, monitoring is carried out by foster caregivers by comparing the results of previous monitoring regarding the development of students. learning evaluation, carried out with a test system both written and oral tests regarding the knowledge of reading al-quran and furudul ʻainiyah. If the student passes the test, the student will move to the dormitory of their respective institution. if they do not pass, the students will continue to follow coaching for the next in the I'dadiyah institution.